2017
DOI: 10.3390/ijerph14091044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bisphenol A on Puberty: A Critical Review of the Medical Literature

Abstract: Many scientific studies have revealed a trend towards an earlier onset of puberty and have disclosed an increasing number of children that display precocious puberty. As an explanation, some authors have considered the global socio-economic improvement across different populations, and other authors have considered the action of endocrine disrupting chemicals (EDCs). Among these, bisphenol A (BPA), an aromatic compound largely used worldwide as a precursor of some plastics and chemical additives, is well known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 152 publications
1
33
0
21
Order By: Relevance
“…In fact, in contrast to the conclusion of official reports on EDCs [ 1 2 5 ], many recent systemic reviews or meta-analyses focusing on epidemiological studies, especially of short-lived EDCs, seem to support the opponents' position. For example, reviews of the effects of bisphenol A (BPA) in humans reported conflicting results with respect to pubertal development [ 22 ] and diabetes [ 23 ]. Similar conclusions have been reached on phthalate and obesity [ 24 ], triclosan and diverse health effects [ 25 ], and developmental exposure to many EDCs and male reproductive disorders [ 26 ].…”
Section: Debates About the Evidence Of Harm To Humansmentioning
confidence: 99%
“…In fact, in contrast to the conclusion of official reports on EDCs [ 1 2 5 ], many recent systemic reviews or meta-analyses focusing on epidemiological studies, especially of short-lived EDCs, seem to support the opponents' position. For example, reviews of the effects of bisphenol A (BPA) in humans reported conflicting results with respect to pubertal development [ 22 ] and diabetes [ 23 ]. Similar conclusions have been reached on phthalate and obesity [ 24 ], triclosan and diverse health effects [ 25 ], and developmental exposure to many EDCs and male reproductive disorders [ 26 ].…”
Section: Debates About the Evidence Of Harm To Humansmentioning
confidence: 99%
“…Despite some differences in urinary concentrations of BPA and estrogens between the groups, our study found limited evidence that these concentrations explained the association between exposure to the UK environment and earlier thelarche. Evidence concerning the relationship between BPA and pubertal outcomes has been mixed [11]. Several toxicological studies have reported that early exposure to low doses of BPA altered the development of rodent mammary glands, which manifested from the time of exposure and was exacerbated at puberty and beyond [31].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest BPA demonstrates estrogenic activity [8], accelerates pubertal onset [9], and increases mammary cancer risk [10]. However, epidemiological evidence between BPA and puberty has been mixed [11]. Nevertheless, the World Health Organization commissioned a report in 2012 on endocrine-disrupting chemicals and recommended research should investigate whether early-life exposures are associated with changes in the timing of pubertal events [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in rats, neonatal exposure to BPA for 2 weeks led to delayed puberty at a low dose, but earlier puberty when a higher dose was administered. Similarly, lower doses of phthalates were associated with early puberty, whereas the opposite effect was observed with higher doses (39). Second, timing of exposure has a substantial effect on the final outcome.…”
Section: Endocrine Disruptorsmentioning
confidence: 97%